Computational Forensic Authorship Analysis: Promises and Pitfalls - Argamon, Shlomo Engelson (Language and Law / Linguagem e Direito, 2019)
The authorship of questioned documents often constitutes important evidence in criminal and civil cases. Linguistic stylistic analysis can often help to determine authorship. Computational methods have been applied to authorship analysis in academia for decades, and in recent years have achieved the levels of reliability needed for application to real-world cases. This article surveys the dierent types of computational authorship analysis methods and their components in a practical vein—describing the assumptions each makes, the analytic controls they require, and the tests needed to measure and ensure their reliability. Specically, I discuss many of the potential pitfalls in their application, to guide practitioners in more eectively achieving trustworthy and understandable results. It must always be remembered, though, that there is no substitute for expertise, experience, and careful human judgment.